Rheumatoid arthritis therapy with genetically engineered biological agents in the Republic of Karelia - Irina Mikhailovna Marusenko; И. М. Марусенко (Modern Rheumatology Journal, 2013)
The paper considers whether a current treatment option for rheumatoid arthritis with genetically engineered biological agents that selectively block the activity of individual proinflammatory mediators and cell surface antigens involved in autoimmune inflammation may be performed in Karelia, which can achieve control of the disease, retard its progression, and improve prognosis. Статья посвящена возможностям реализации в Карелии современного направления в лечении ревматоидного артрита – применения генно-инженерных биологических препаратов, которые селективно блокируют активность отдельных провоспалительных медиаторов и поверхностные антигены клеток, участвующих в аутоиммунном воспалении, что позволяет достичь контроля над заболеванием, замедления его прогрессирования и улучшения прогноза.